Experiment measurements for packet reception rate in wireless underground sensor networks - Ahmed, Adel Ali (Academy Publisher, 2009)
A Wireless Underground Sensor Network (WUSN) is a network of wireless sensor devices in which all sensor devices are deployed completely underground (network sinks or any devices specifically for relay between sensors and a sink may be aboveground). These networks can be utilized to monitor the underground environment, especially soil conditions and aboveground events, such as the presence of people or animals. This paper measures the path loss exponent and packet reception rate for underground environment using test bed experiment work. The signal strength of the signal propagation is measured underground and aboveground.